Schwannoma of Cheek Mucosa - Kaur, Anureet; Kaur, Puneet; Sarin, Rimpi (International Journal of Pathology, 2018)
Schwannoma is a relatively uncommon, benign, encapsulated, slow growing, usually solitary tumour that originates from Schwann cells of the nerve sheath derived from the neuroectoderm. Only 1% of Schwannomas have intra-oral of which most common site is tongue followed by the palate, floor of mouth, buccal mucosa, lips and jaws. We report a case of Schwannoma in cheek mucosa within oral cavity which was surgically removed and on histopathological examined revealed Schwannoma with Antoni A and Antoni B patterns with Verocay body formation